Tinjauan Yuridis Terhadap Undang Undang Nomor 4 Tahun 2016 Tentang Tabungan Perumahan Rakyat (Tapera) - Kadek Apriliani; I Gusti Ayu Sita Maharani; Dennis Santoso Ratu (Faculty of Law, Mahasaraswati University, Denpasar, 2024)
This study examines Law No. 4 of 2016 and Government Regulation No. 21 of 2024 regarding Tapera (Tabungan Perumahan Rakyat) and evaluates the legal protection for participants in disputes using a normative method. The focus of this research is on the alignment of Tapera regulations with the principles of social justice within the Indonesian legal system. The findings indicate that Tapera is designed to meet the housing needs of low-income communities, reduce socio- economic disparities, and ensure transparency and accountability in fund management. However, the policy has been criticized for imposing significant salary deductions on workers, especially during difficult economic conditions. Legal protection for participants, including clear and transparent dispute resolution mechanisms, is essential to ensure fairness and security. This study concludes that improvements in the implementation of Tapera are necessary to achieve the national housing goals equitably and fairly.